Моделювання середовищ із заданим коефіцієнтом заломлення - Андрійчук, М.І. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
A combination of asymptotic approach and computational modeling is used for solution of problem to create the media with the prescribed electrodynamic characteristic, in particular, a refraction coefficient. The initial diffraction problem is considered under the assumptions ka << 1, d >> a, where a is the size of the particle and d is the distance between the neighboring particles. Impedance boundary conditions are assumed on the boundaries of small particles. The results of numerical simulation show good agreement with the theory. They open a way to numerical implementation of the method for creating media with a desired refraction coefficient.